Efektivitas Penggunaan Pendekatan Slim-N-Bil Terhadap Pemahaman Konsep Matematika - Indra Martha Rusmana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
The concept is one of the foundations of mathematics in the study of mathematics, if the concept is given to students not to good, then the result of learning and understanding of learners in the materials will be reduced. Mathematical concepts can be supplied with a variety of approaches so that learners are able to understand the material provided by the teacher, one of the mathematical learning approach is SLIM-n-BIL. The purpose of this study is to determine the effect and effectiveness of the approach using Slim-n-Bil to the understanding of the concept of junior high school math learners. This study used a quasi-experimental methods are implemented in SMP Mahardika with data retrieval through essay questions. Hypothesis testing is performed using the software SPSS 17.0 for windows at significance level of 0.05. This study resulted in two main conclusions, namely; First, there is the effect of the use of the SLIM approach-n-BIL to the understanding of mathematical concepts as tcount obtained for 0.895 less than the 2,000 ttable with Sig. 0.138> ? (0.05); second, SLIM approach-n-BIL effective in improving student understanding of mathematical concepts as values obtained effect size of 0.231.